Penerimaan organoleptik snack bar berbahan tepung ayam, sorgum, dan daun kelor untuk ibu hamil KEK - Elvika Fit Ari Shanti; Tri Sunarsih; Endah Puji Astuti; Bangun Prajanto Nusantoro (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Pregnant women with Chronic Energy Deficiency (CED) need a balanced nutritional intake to support fetal development and maternal health. However, limited access and choice of nutritious food is a challenge that needs to be overcome.Objective: This research aims to develop a snack bar product from Chicken Flour, Sorghum Flour, and Moringa Leaves as additional food for pregnant women with CED.Method: The research design was used experimentally with a Completely Randomized Design (CRD). The experimental unit in this research is the snack bar product. The study was carried out in three stages: making moringa flour, chicken flour, and sorghum flour. Second: determining the formula. Third, organoleptic tests and the acceptability of the selected formula are carried out. Respondents with trained panelists totaled 30 panelists. The statistical test used is the Kruskal-Wallis test.Results: The most frequent organoleptic test results are brown and attractive in L2 19 respondents (56.7), the most common taste is naturally sweet and savory and liked by L2 17 respondents (56.7), the most common aroma is balanced and not too strong, typical of herbal L2 18 respondents (60.0), and the most common texture was slightly tricky, crunchy solid L3 12 respondents (40.0). Meanwhile, the highest level of acceptance of color in the like category was L1 20 respondents (66.7), taste in the like category was L2 20 respondents (66.7), the aroma in the like category was L3 20 respondents (66.7), and the average texture in the like category was L1 15 respondents (50.0), L2 15 respondents (50.0) and L3 15 respondents (50.0). The results of the Kruskal Wallis test showed that the different ratios of chicken flour, sorghum flour and moringa leaves had a significant effect on the organoleptic test of color, taste, aroma (p<0.05).Conclusion: The best snack bar product development, formula L2, showed the best results in terms of taste, aroma, texture, and appearance.